2021
DOI: 10.3389/fcimb.2021.638852
|View full text |Cite
|
Sign up to set email alerts
|

The Weight of Obesity in Immunity from Influenza to COVID-19

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has emerged in December 2019 and rapidly outspread worldwide endangering human health. The coronavirus disease 2019 (COVID-19) manifests itself through a wide spectrum of symptoms that can evolve to severe presentations as pneumonia and several non-respiratory complications. Increased susceptibility to COVID-19 hospitalization and mortality have been linked to associated comorbidities as diabetes, hypertension, cardiovascular diseases and, recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 202 publications
(245 reference statements)
0
28
0
Order By: Relevance
“…Morbidity and mortality from CoVID-19 are further increased in subjects with obesity with visceral adiposity and ectopic fat deposition [ 60 ]. Therefore, individuals with obesity are assumed to develop more severe CoVID-19 disease than normal-weight individuals, regardless of gender, age, and existence of associated comorbidities [ 61 63 ]. Similarly, in a cohort of 200 hospitalized patients, in USA, with CoVID-19 in a minority-predominant population, severe obesity, increasing age, and male sex were independently associated with higher in-hospital mortality and in general worse in-hospital outcomes [ 64 ].…”
Section: Obesity and Covid-19: Human Evidencementioning
confidence: 99%
“…Morbidity and mortality from CoVID-19 are further increased in subjects with obesity with visceral adiposity and ectopic fat deposition [ 60 ]. Therefore, individuals with obesity are assumed to develop more severe CoVID-19 disease than normal-weight individuals, regardless of gender, age, and existence of associated comorbidities [ 61 63 ]. Similarly, in a cohort of 200 hospitalized patients, in USA, with CoVID-19 in a minority-predominant population, severe obesity, increasing age, and male sex were independently associated with higher in-hospital mortality and in general worse in-hospital outcomes [ 64 ].…”
Section: Obesity and Covid-19: Human Evidencementioning
confidence: 99%
“…Transcriptomic studies have identified both absent/low and increased IFN response genes in patients with severe or lethal disease, and longitudinal studies revealed a diminished and/or delayed induction of type I IFNs in COVID-19 patients compared with patients with influenza, with an exuberant early TNF/IL6 response 16 . To date, the effect of obesity on immune responses to SARS-CoV-2, particularly tissue responses, has not been considered, although it has been proposed that the elevated leptin associated with obesity might promote an excessive inflammatory response, contributing to the worse outcomes observed in obese patients with COVID-19, with calls for anti-inflammatory therapeutic strategies to be employed in this patient group 17 .…”
Section: Mainmentioning
confidence: 99%
“…Nevertheless, when obesity is present, the low-grade state of inflammation in both omental and subcutaneous adipose tissues often results in impaired glucose metabolism and may contribute to the development of insulin resistance and weight gain. Moreover, obesity and insulin resistance further compromise the already impaired immune systems ( Andrade et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%